MANITORING OF PHYSICAL FITNESS AND FUNCTIONAL STATE OF THE ORGANISM OF ELEMENTARY STUDENTS IN THE GENERAL EDUCATIONAL SCHOOL SYSTEM (Scientific journal of the Fergana State University, 2023)
The purpose of the study is to assess the physical and functional condition of younger schoolchildren aged 7-10 years. The study was conducted with the participation of healthy children aged 7-10 years, studying at an educational institution in Ferghana, who do not have medical contraindications to physical education. The complex of control exercises consisted of indicators characterizing the level of development of coordination motor abilities. Functional indicators were determined. The graduation of all students according to the level of physical readiness for all motor tests and the level of functional readiness was also carried out.